Erratum: Publisher's Note: "Magneto-responsive hyaluronan hydrogel for hyperthermia and bioprinting: Magnetic, rheological properties and biocompatibility" [APL Bioeng. 7, 036113 (2023)] - Vítková, L; Kazantseva, N; Musilová, L; Smolka, P; Valášková, K; Kocourková, K; Humeník, M; Minařík, A; Humpolíček, P; Mráček, A; Smolková, I (APL bioengineering, 2024)
[This corrects the article DOI: 10.1063/5.0147181.].